Referral parameters for diagnosis of glaucoma in general eye clinic at Tilganga Institute of Ophthalmology - Joshi, Pratibha Lama; Jha, Bhaskar; Paudyal, Indira; Thapa, Suman Shamsher (Nepalese Journal of Ophthalmology, 2019)
Objective: To find out the most common referral parameter among the glaucoma suspects patients from general eye clinic and to establish glaucoma diagnosis.Methods: This study is a retrospective cohort hospital based study. Two hundred patients from January to February 2017 sent to glaucoma clinic as glaucoma suspects were re-evaluated meticulously by glaucoma specialist and were diagnosed as glaucoma, non glaucoma, suspects and ocular hypertension.Results: Out of the 200 patients referred to glaucoma clinic as glaucoma suspects only19% were diagnosed to have glaucoma. The mean age at which glaucoma diagnosed was 55.29(14.4) compared to 41.6(15.1) in normal group. One hundred and sixty five patients were referred on the basis of suspicious optic nerve head, among them 14.5% (24/165) had glaucoma. This study showed that, open angle glaucoma (OAG) 28.9% was the most common type of total glaucoma diagnosed. The mean vertical cup discratio in the OAG group was 0.69±0.1 (0.4 -0.9) compared to 0.56 ± 0.11((0.2-0.8)(p=0.00) normal. The mean intra ocular pressure (IOP) in OAG group was 19.73 ±4.95(11-32) mmHg compared to 16.74± 3.36(10-30) mmHg (p=0.00) in normal group. The mean central corneal thickness (CCT) in OAG group was 533.05 ± 31.24μm (467-606) compared to normal was 534.9±33.6 μm (432-696) (p=0.670).Conclusions: Suspicious optic nerve head is the most common referral parameter between the general ophthalmologist and residents, but this study shows only few of them were diagnosed with glaucoma. This gives us a clue that the ophthalmologists and residents are to be trained better to help them identify the signs of glaucoma on the optic nerve head beside its size, which will reduce unnecessary burden to the resources of patients and hospital.